The Chlamydomonas mex1 mutant shows impaired starch mobilization without maltose accumulation. (5th October 2017) - Findinier, Justin; Tunçay, Hande; Schulz-Raffelt, Miriam; Deschamps, Philippe; Spriet, Corentin; Lacroix, Jean-Marie; Duchêne, Thierry; Szydlowski, Nicolas; Li-Beisson, Yonghua; Peltier, Gilles; D'Hulst, Christophe; Wattebled, Fabrice; et al.
Abstract : The Chlamydomonas MEX1 locus encodes a plastid-targeted protein that is required for starch degradation but unable to transport maltose efficiently. Abstract: The MEX1 locus of Chlamydomonas reinhardtii was identified in a genetic screen as a factor that affects starch metabolism. Mutation of MEX1 causes a slow-down in the mobilization of storage polysaccharide. Cosegregation and functional complementation analyses were used to assess the involvement of the Mex1 protein in starch degradation. Heterologous expression experiments performed in Escherichia coli and Arabidopsis thaliana allowed us to test the capacity of the algal protein in maltose export. In contrast to the A. thaliana mex1 mutant, the mutation in C. reinhardtii does not lead to maltose accumulation and growth impairment. Although localized in the plastid envelope, the algal protein does not transport maltose efficiently across the envelope, but partly complements the higher plant mutant. Both Mex orthologs restore the growth of the E. coli ptsG mutant strain on glucose-containing medium, revealing the capacity of these proteins to transport this hexose. These findings suggest that Mex1 is essential for starch mobilization in both Chlamydomonas and Arabidopsis, and that this protein family may support several functions and not only be restricted to maltose export across the plastidial envelope.